Infective Endocarditis in 60 Years Old Man at Dr. Kariadi Hospital - Wahyutomo, Ridha (Fakultas Kedokteran; Universitas Islam Sultan Agung (UNISSULA), 2013)
Infective endocarditis is an infection of the lining of the heart, particularly the cusps of valves characterized by fever and heart murmur, with or without malaise and fatigue. Clinical features can be divided into early manifestations of infection, embolic events, and late complications of sepsis and inflammation. It was reported that 60 years old man was brought to Kariadi hospital with prolong febris as his chief complaint. Patient has history of high grade fever and accompanied by weight loss, 3 kilograms for about 2 months. From physical examination result, in internal ward, we found he looked moderate ill. Heart systolic bruit at triscupidal valve and lungs were within normal limit. The result of blood culture from 3 different sites and throat swab culture were possitive, lead to the performance Streptococcus b haemolyticus’s colonies. From the result of the ASTO, Echocardiography and physical examination show infective endocarditis’s sign. The theraphy was Ceftriaxone 2 gram daily. Having obtained the results of negative cultures, and show an improvement of symptoms, finally the patient was getting improvement clinically and then treat as an outpatient. Patient was programmed to get Ceftriaxone 2 gram daily for 4 weeks. The decision of treatment not only from clinical manifestation but also from microbiology examination on the first admission in emergency unit. Blood culture with 3 bottles, interval 30 minutes is important for infective endocarditis. Furthermore, swab of throat area were taken to confirm for endocarditis cultures too. Finally there is no growth in culture until eighth day hospitalizasition. Spesific method on blood culture sampling is important to confirm the diagnostic of infective endocarditis and very useful for the clinicians to do the right clinical management for it. Subsequently, the role of clinical microbiologist in this case not only to support the clinical diagnostic but also the treatment in term of selecting of right antibiotic.